2003
DOI: 10.1007/bf02709777
|View full text |Cite
|
Sign up to set email alerts
|

Indian monsoon variability in relation to Regional Pressure Index

Abstract: In this paper Regional Pressure Index (RPI) over the Indian region (20 • N-40 • N and 70 • E-85 • E) has been constructed for 101 years (1899-1999) on a monthly scale. The relationship of these indices was carried out with the Indian Summer Monsoon Rainfall (June-September) (ISMR) over the various homogeneous regions, for all the time scales. From the analysis it has been seen that RPI in the month of May is significantly associated with ISMR over various regions on all the scales. The relationship is statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Rajeevan, 2001;Pai and Rajeevan, 2006;Goswami and Gouda, 2007;Raju et al, 2007). Studies explored that the Indian monsoon is more heterogeneous mainly due to its dependence on atmospheric (Dugam and Kakade, 2003) and oceanic (Pattanaik and Rajeevan, 2007) influences.…”
Section: Introductionmentioning
confidence: 98%
“…Rajeevan, 2001;Pai and Rajeevan, 2006;Goswami and Gouda, 2007;Raju et al, 2007). Studies explored that the Indian monsoon is more heterogeneous mainly due to its dependence on atmospheric (Dugam and Kakade, 2003) and oceanic (Pattanaik and Rajeevan, 2007) influences.…”
Section: Introductionmentioning
confidence: 98%
“…Various studies on rainfall trends have also been carried out in in India [GUHATHAKURTA, RAJEEVAN 2008;KOTHYARI, SINGH 1996;PAR-THASARATHY, DHAR 1974;1978;SARKAR et al 2004;SEN ROY, BALLING 2004], and it has been reported that Indian monsoon rainfall is strongly affected by atmospheric factors viz. regional pressure anomalies [DUGAM, KAKADE 2003], cyclonal activities [PAT-TANAIK, RAJEEVAN 2007] and sea surface temperature variations [GOSWAMI et al 2006], thereby making monsoon rainfall less predictable [MANI et al 2009]. PATTANAIK, RAJEEVAN [2010] assessed long term trends in the Indian monsoon season from 1951 to 2005, and found extreme rainfall events increased and low rainfall events decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Indian monsoon rainfall is highly influenced by atmospheric factors such as regional pressure anomalies [61], cyclonal activities [62] and sea surface temperature variations [63]. Rainfall pattern of past North-west region which is the key to trigger monsoon, has recorded moderate while the Southern region has recorded a very significant rise in temperature during the past century.…”
Section: Climate Change In Indian Perspectivementioning
confidence: 99%